2022
DOI: 10.1007/s00264-022-05313-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for second-stage posterior direct decompression after lateral lumbar interbody fusion: a review of five hundred fifty-seven patients in the past five years

Abstract: Purpose To analyze the predictors for second-stage posterior direct decompression (PDD) after lateral lumbar interbody fusion (LLIF) procedure. Methods We studied patients who underwent LLIF for degenerative lumbar spinal stenosis in the last five years, from July 2016 to June 2021. All surgical levels were grouped according to Schizas’ central canal stenosis (CCS) classification, Pathria’s facet joint degeneration (FJD) classification, Bartynski’s lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…To some extent, these can relieve the patient's symptoms in OLIF [23]. However, sometimes OLIF alone had no improvement of neurologic symptoms due to the inadequate decompression such as extreme severe lumbar canal stenosis and bony lateral recess stenosis [10,12,[24][25][26][27]. When the segment is too rigid to be restored, it is difficult to obtain a greater postoperative disc height and more indirect decompression effect [28].…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, these can relieve the patient's symptoms in OLIF [23]. However, sometimes OLIF alone had no improvement of neurologic symptoms due to the inadequate decompression such as extreme severe lumbar canal stenosis and bony lateral recess stenosis [10,12,[24][25][26][27]. When the segment is too rigid to be restored, it is difficult to obtain a greater postoperative disc height and more indirect decompression effect [28].…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, this can relieve the patient's symptoms (22). However, sometimes OLIF alone had no improvement of neurologic symptoms because of the inadequate decompression (10,23). The study of Li et al (23) showed that the overall posterior direct decompression rate after OLIF was 29.97%, and extreme severe lumbar central canal stenosis is the greatest determinant to perform the second-stage posterior direct decompression procedure after OLIF.…”
Section: Discussionmentioning
confidence: 99%
“…However, sometimes OLIF alone had no improvement of neurologic symptoms because of the inadequate decompression (10,23). The study of Li et al (23) showed that the overall posterior direct decompression rate after OLIF was 29.97%, and extreme severe lumbar central canal stenosis is the greatest determinant to perform the second-stage posterior direct decompression procedure after OLIF. Lim et al (24) and Yingsakmongkol et al (25) found that persistent pain despite resting in a supine position suggests the presence of severe spinal canal stenosis with significant static nerve compression that would only be sufficiently relieved with a direct decompression after extreme lateral interbody fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Hayama et al [21] reported that after they determined the insufficient neural decompression status through intraoperative CT myelogram, they performed further direct posterior decompression and achieved favorable results. Additionally, Li et al [18] reported that extremely severe lumbar central canal stenosis is the main indication for second-stage posterior direct decompression after LLIF. Similarly, we assessed whether the spaceoccupying stenotic or disk lesion remains in the spinal In our cases, hard stenotic lesion and ligamentum flavum thickening could be removed by BEPD, and the patients' symptoms were relieved.…”
Section: Discussionmentioning
confidence: 99%